On the right of arbitration courts to consider individual labor disputes - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2019)
The question of the possibility of arbitration courts to consider individual labor disputes is being investigated. The author analyzes the current legislation, scientific points of view, law enforcement practice, legal positions of the Constitutional Court, and comes to the conclusion that arbitration courts have the right to consider individual labor disputes. In this regard, the author proposes to introduce a number of changes and additions to the legislation, in particular, to indicate in the labor legislation arbitration courts among the bodies for the consideration of labor disputes; to list categories of non-arbitrage labor disputes; to clarify the regulation of issues of invalidity of the arbitration agreement; to change approaches to regulating the derogation action of the arbitration agreement; to improve the order of interaction of the arbitration and judicial forms of protection of the right on the issues of proof and evidence, securing the claim, prejudiciality, execution of arbitral awards.
Keywords: individual labor disputes; arbitration court; the state court; civil legal proceedings; jurisdiction; arbitrability